2010
DOI: 10.1111/j.1468-2958.2010.01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Institutional and Noninstitutional Influences on Information and Communication Technology Adoption and Use Among Nonprofit Organizations

Abstract: In this study, nonprofit organizations (NPOs) in New Zealand were surveyed to explore influences on adoption and use of information and communication technologies (ICTs). We sought to extend existing research by considering ''institutional'' influences alongside organizational and environmental features and by examining how institutional forces affect optimal use of ICTs. Findings suggest that NPOs adopting and using ICTs tended to be self-perceived leaders or those who scanned the environment and emulated lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 57 publications
4
88
0
4
Order By: Relevance
“…Whereas some charities make good use of IT and there is some evidence of IT positively impacting on charity performance (Kobelsky et al 2014), its strategic application is generally under-exploited (Hackler and Saxton, 2007;Zorn et al, 2011). There are also many barriers and constraints for effective use of IT in charities (Clerkin and Grønbjerg, 2007;Cortés and Rafter, 2007;Wolpert and Seley, 2007;Manzo and Pitkin, 2007).…”
Section: Ask "How Do (Or Can) Tsos Strengthen Their Reporting So Thatmentioning
confidence: 99%
“…Whereas some charities make good use of IT and there is some evidence of IT positively impacting on charity performance (Kobelsky et al 2014), its strategic application is generally under-exploited (Hackler and Saxton, 2007;Zorn et al, 2011). There are also many barriers and constraints for effective use of IT in charities (Clerkin and Grønbjerg, 2007;Cortés and Rafter, 2007;Wolpert and Seley, 2007;Manzo and Pitkin, 2007).…”
Section: Ask "How Do (Or Can) Tsos Strengthen Their Reporting So Thatmentioning
confidence: 99%
“…Using institutional theory to investigate the forces that influence the adoption and use of IT in nonprofits, Zorn, Flanagin and Shoham (2011) found that leadership support and professional IT staff engagement were significant factors. In a similar study, Jaskyte (2011) also found that transformational leadership contributed significantly to technological innovation in nonprofit organizations.…”
Section: Institutional Theorymentioning
confidence: 99%
“…The diffusion of social media among nonprofits is important to study since the widespread growth of social media has fundamentally influenced nonprofit organizations' communication and management practices. Nonprofits use social media platforms to promote and maintain their programs and services by reaching out to new constituents through cyberspace (Krestalude, 2011;Zorn, Flanagin, and Shoham, 2011). The social media use can enhance the nonprofit organizations' service delivery and the mobilization of their clients and supporters.…”
Section: The Dartmouth Center For Marketing Research At the Universitmentioning
confidence: 99%
See 2 more Smart Citations